“From Homer to Hermoniakos: Some Considerations of Troy Matter in Byzantine Literature” - Nilsson, Ingela (Troianalexandrina, 2004)
Abstract A number of authors in Byzantium remodelled Homeric and non-Homeric material in different manners, not only citing and alluding to the epics but also discussing and remodelling the subject matter. Byzantine Troy matter appears in the chronographical tradition, in a series of commentaries and paraphrases, and in romances and other texts belonging to the “novelistic fringe”. Drawing basically on Homeric and post-Homeric legends, these texts are to different degrees intrinsically interrelated not only to each other, but also to the so-called Komnenian novels and to the Western Troy matter in Benoît de Sainte-Maure’s Roman de Troie. The present article attempts to briefly outline the complex relations between the texts and to consider the links between ancient and Medieval, Western and Byzantine, epic, history, and novel.